On the structure of some non-periodic groups whose subgroups of infinite special rank are transitively normal - Velychko, T.V. (Доповіді НАН України, 2021)
A group G has a finite special rank r, if every finitely generated subgroup of G can be generated by at most r elements, and there exists a finitely generated subgroup H which has exactly r generators. This paper is devoted to genera lized radical non-Abelian groups of infinite special rank whose subgroups of infinite special rank are transitively normal. Група G має скінченний спеціальний ранг r, якщо кожна скінченно породжена підгрупа G може бути породжена не більш ніж r eлементами та існує скінченно породжена підгрупа H, яка має точно r породжуючих eлементів. У статті наведено опис узагальнених радикальних неабелевих груп, в яких підгрупи нескінченного спеціального рангу є транзитивно нормальними.